Ocorrência da raiva e de anticorpos antirrábicos em morcegos do noroeste de São Paulo - Casagrande, Daiene Karina Azevedo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Rabies is a major zoonosis which affects mammals from all over the world and has bats as reservoirs of, both urban and rural areas. Since 1998 cases of rabies in bats have been recorded in the northwest region of São Paulo State, predominantly in urban areas. The objective of this study was to investigate the circulation of rabies in bats in the northwestern region of São Paulo by searching of the virus in different species and the presence of rabies neutralizing antibodies in vampire bats. A total of 1,490 brain samples from bats were sent to the Laboratory of Rabies and 125 serum samples of vampire bats from four shelters in the region were examined from 2008 to 2012. The virus presence was determined by fluorescent antibodies test (FAT) and mouse inoculation test (MIT) while neutralizing antibodies were determined by the simplified microneutralization (SFIMT) in BHK21 cells. Rabies virus was detected in 26 (1.97%) out of 1,314 non-hematophagous bats and in none of the 176 vampire bats examined. Only 7% (9/125) of vampire bats had antibody titers above 0.5UI/ml, 65% (81/125) had low titers (0.10 to 0.5UI/ml) and 28% (35/125) were negative. The positivity rate observed was 1.74% which is above the average rate of 1.3% recorded previously in this region. The high percentage of vampire bats with neutralizing antibodies to rabies virus indicates a recent exposure to the virus which confirms that surveillance measures must be in place to avoid an increase in disease occurrence
Keywords: Morcego; Vírus da hidrofobia; Imunoglobulinas; Sorologia veterinaria; Pesquisa experimental; Antibodies